CHANGING WORLD ORDER AND THE EMERGING ECONOMIES - Dahiya, Khushbu; Kumar, Pardeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The global order is undergoing a transformative shift as emerging economies such as China, India, Brazil, and South Africa redefine global power dynamics. These nations, once marginal in global decision-making, are now reshaping international relations through sustained economic growth, technological innovation, and demographic advantages. Their growing influence is evident in platforms like BRICS, the Shanghai Cooperation Organization, and the Asian Infrastructure Investment Bank, which advocate for inclusive governance and challenge Western-dominated institutions. The rise of these economies reflects a broader transition from a unipolar to a multipolar world, driven by globalization and strategic initiatives like China’s Belt and Road Initiative and India’s Act East Policy. While their ascent offers opportunities to address global inequalities and enhance South-South cooperation, it also brings challenges such as internal disparities, environmental pressures, and external geopolitical rivalries. The evolving responses of established powers, including strategic partnerships and attempts at containment, underscore the contested nature of this transition. Emerging economies are central to shaping a more balanced and cooperative global order, offering both opportunities and complexities in navigating the realities of the 21st century.